If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 79 = 10x + -12 Reorder the terms: 79 + 3x = 10x + -12 Reorder the terms: 79 + 3x = -12 + 10x Solving 79 + 3x = -12 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 79 + 3x + -10x = -12 + 10x + -10x Combine like terms: 3x + -10x = -7x 79 + -7x = -12 + 10x + -10x Combine like terms: 10x + -10x = 0 79 + -7x = -12 + 0 79 + -7x = -12 Add '-79' to each side of the equation. 79 + -79 + -7x = -12 + -79 Combine like terms: 79 + -79 = 0 0 + -7x = -12 + -79 -7x = -12 + -79 Combine like terms: -12 + -79 = -91 -7x = -91 Divide each side by '-7'. x = 13 Simplifying x = 13
| 5y+9+-4x-5y=0 | | -3x+-18y=0 | | 2/3x-1/6=0.5 | | -3x=-18y | | 0.67j-1/6=0.5 | | 6.7X+3=5.7X | | 3x-6+3yi=-3i | | 2(n-5)-(7-n)= | | 9(n+9)+4(n-1)= | | 5(n+3)+6(n+2)= | | 4e-3(2e-2)=3e+24 | | -28x=84 | | 9(6x-2)= | | 2x+22=7x+95 | | 10(x+1)=7(x+16) | | 8(3x-2)=2(12x+7) | | 4+3m-2=9m+29-3m | | -8+9=0 | | 1-(5x-8)/9=(x+3)/4 | | 1-5x-8/9=x+3/4 | | 3x-1/4-2x+1/5=7x-13/20 | | 9p+8p= | | 2+6(t-4)=4(t-6)+8 | | y+4-4=3x-9-4 | | 4q+6=-3q-43 | | -2m+7=2m-1 | | 5h=4x | | 8e-3=5e-9 | | 17d-3=9d+45 | | 2p+9=6p-27 | | 9t+10t=38 | | -c+2=-6c-13 |